KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA PEMBUAT MAKANAN OLAHAN TERHADAP PENDAPATAN KELUARGA - Handayani, M.Th.; Artini, Ni Wayan Putu (PIRAMIDA; Vol. 5, No.1 Juli 2009)
The uncertainly of the economic condition where the chance of employment is limitedhas led to the stability of family source of income. This condition has pushed haousewifeswhere previously just conserned on domestic matters to public sector partisipation tosupport family income. This research aimed at finding contribution of housewife workersincome by processing food to the total family income. This research was conducted atPemogan village, South Denpasar district, Province of Bali.This result of the research shows that type of job done by housewife worker were infood industries with the average time alocation for processing food accounts for 4.27hours per day. It was also found that the average of earning per month is Rp.429,753.00 andit amounts is 12.82% of the total family’s income. This implies that labor produvtivity isRp3,594.00 per hour. The reasons wife working are (a) to support family income, (b) to fillsparetime with positive activities, (c) to look for an experiences. About 83,3% housewifeworker doesn’t find difficulties for processing food, only a small amount (16,7%) findsdifficulties.In order to improve the contibution of houswife worker to the family income, it issuggested to guide them for better processing methodes and management by relatedinstitutions. This includes Bali Agricultural office and BPTP.
Keywords: Houewife worker, contribution, total family income, food processing